O-GlcNAcylation in ovarian tumorigenesis and its therapeutic implications - Lu Xia; Jie Mei; Min Huang; Dandan Bao; Zhiwei Wang; Yizhe Chen (Translational Oncology, 2025)
Ovarian cancer is a prevalent malignancy among women, often associated with a poor prognosis. Post-translational modifications (PTMs), particularly O-GlcNAcylation, have been implicated in the progression of ovarian cancer. Emerging evidence indicates that dysregulation of O-GlcNAcylation contributes to the initiation and malignant progression of ovarian cancer. This review discusses the potential role of O-GlcNAcylation in ovarian tumorigenesis, with a focus on its regulation of various cellular signaling pathways, including p53, RhoA/ROCK/MLC, Ezrin/Radixin/Moesin (ERM), and β-catenin. This review also emphasizes the O-GlcNAcylation of critical proteins in ovarian cancer, such as SNAP-23, SNAP-29, E-cadherin, and calreticulin. Additionally, the potential of O-GlcNAcylation to enhance immunotherapy for ovarian cancer patients is explored. Several compounds targeting OGT and OGA in ovarian cancer are also highlighted. Targeting the dynamic and versatile nature of O-GlcNAcylation could undoubtedly contribute to more effective treatments and improved outcomes for ovarian cancer patients.